Dirasac in Economics and Business AUDITING ELECTRONIC DATA PROCESSING (EDP) SYSTEMS - El - Sharif, Dr. Younis H. (Dirasat in Economics and Business, 1979)
'Throughout history, the total structure of society and the practice of accounting have run in the same direction. Many factors : economical, sociological, legal, and technological have influenced the development of public accounting practices. Technology is one of the most important factors that in fluence the public accounting practices in this country. Although technology already exists for revolutionizing the in formation collection, which is the heart of the accounting func tion, the very speed of technological change is increasing at a geometric rate of growth. As a result, most data processing sys tems of today cover all activities of the business and they are integrated into one computerized system. Manual accounting systems have become as obsolete in these days as single-entry bookkeeping, and even the smallest business organization uses some kind of automated procedures in its accounting work.